Photosensitive and Conductive Hydrogel Induced Innerved Bone Regeneration for Infected Bone Defect Repair. Issue 3 (14th November 2022) - Jing, Xirui; Xu, Chao; Su, Weijie; Ding, Qiuyue; Ye, Bing; Su, Yanlin; Yu, Keda; Zeng, Lian; Yang, Xu; Qu, Yanzhen; Chen, Kaifang; Sun, Tingfang; et al.
Abstract: Repairing infected bone defects is a challenge in the field of orthopedics because of the limited self‐healing capacity of bone tissue and the susceptibility of refractory materials to bacterial activity. Innervation is the initiating factor for bone regeneration and plays a key regulatory role in subsequent vascularization, ossification, and mineralization processes. Infection leads to necrosis of local nerve fibers, impeding the repair of infected bone defects. Herein, a biomaterial that can induce skeletal‐associated neural network reconstruction and bone regeneration with high antibacterial activity is proposed for the treatment of infected bone defects. A photosensitive conductive hydrogel is prepared by incorporating magnesium‐modified black phosphorus (BP@Mg) into gelatin methacrylate (GelMA). The near‐infrared irradiation‐based photothermal and photodynamic treatment of black phosphorus endows it with strong antibacterial activity, improving the inflammatory microenvironment and reducing bacteria‐induced bone tissue damage. The conductive nanosheets and bioactive ions released from BP@Mg synergistically improve the migration and secretion of Schwann cells, promote neurite outgrowth, and facilitate innerved bone regeneration. In an infected skull defect model, the GelMA‐BP@Mg hydrogel shows efficient antibacterial activity and promotes bone and CGRP + nerve fiber regeneration. The phototherapy conductive hydrogel provides a novel strategy based on skeletal‐associated innervation for infected bone defect repair. Abstract : This study reports a GelMA‐BP@Mg (GBM) hydrogel for antibacterial and innerved bone regeneration of infected bone defects. Under near‐infrared (NIR) irradiation, the GBM hydrogel has high antibacterial efficiency and reduces the damage of bacteria to bone tissue. Magnesium‐modified black phosphorus (BP@Mg) nanosheets promote skeletal‐associated nerve fiber repair and accelerated bone regeneration.